2003
DOI: 10.1177/002215540305100912
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Carbonic Anhydrase XII to the Basolateral Membrane of H+-secreting Cells of Mouse and Rat Kidney

Abstract: S U M M A R YMembrane-associated carbonic anhydrase (CA) has a crucial role in renal HCO 3 Ϫ absorption. CA activity has been localized to both luminal and basolateral membranes of the tubule epithelial cells. CA XII is a transmembrane isoenzyme that has been demonstrated in the basolateral plasma membrane of human renal, intestinal, and reproductive epithelia. The present study was designed to demonstrate the distribution of CA XII expression in the rodent kidney. A new polyclonal antibody to recombinant mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 40 publications
4
59
0
Order By: Relevance
“…Based on the present and previous (Kyllönen et al, 2003) results, kidney appears to contain the highest amount of CA XII. This is in line with the findings by Tü reci et al (1998) and Ivanov et al (1998), who showed high CA XII Fig.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Based on the present and previous (Kyllönen et al, 2003) results, kidney appears to contain the highest amount of CA XII. This is in line with the findings by Tü reci et al (1998) and Ivanov et al (1998), who showed high CA XII Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Kidney served as a positive control for the reagents, which were used to demonstrate CA XII by immunofluorescence in the proximal tubules and in the intercalated cells of the collecting ducts (Kyllönen et al, 2003). This result is confirmed in Figure 2.…”
Section: Distribution Of Ca XII Proteinsupporting
confidence: 57%
See 3 more Smart Citations